2010
DOI: 10.1016/j.jhep.2010.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Impaired homocysteine transsulfuration is an indicator of alcoholic liver disease

Abstract: Background & Aims-Although abnormal hepatic methionine metabolism plays a central role in the pathogenesis of experimental alcoholic liver disease (ALD), its relationship to the risk and severity of clinical ALD is not known. The aim of this clinical study was to determine the relationship between serum levels of methionine metabolites in chronic alcoholics and the risk and pathological severity of ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 35 publications
3
80
0
Order By: Relevance
“…There is no reported evidence to date that folic acid fortification of the diet has reduced the incidence of ALD. However, our recent controlled study found significantly lower levels of serum folate and B6 but higher B12 levels in 40 ALD patients compared to matched healthy control subjects, suggesting a significant effect of associated liver disease on the status of these vitamins [24] .…”
Section: Evidence and Mechanisms For B-vitamin Deficiencies In Chronimentioning
confidence: 72%
See 2 more Smart Citations
“…There is no reported evidence to date that folic acid fortification of the diet has reduced the incidence of ALD. However, our recent controlled study found significantly lower levels of serum folate and B6 but higher B12 levels in 40 ALD patients compared to matched healthy control subjects, suggesting a significant effect of associated liver disease on the status of these vitamins [24] .…”
Section: Evidence and Mechanisms For B-vitamin Deficiencies In Chronimentioning
confidence: 72%
“…Vitamin B6 circulates in the form of protein bound pyridoxal phosphate, and the most widely accepted etiology for vitamin B6 deficiency is the degrading effect of the acetaldehyde product of alcohol metabolism on this compound with subsequent urinary wastage of the free vitamin [49,50] . By contrast, circulating levels of vitamin B12 are often elevated in ALD [21,24] , even though its absorption from the intestine is compromised by chronic alcoholism [51] . This apparent conundrum was resolved by a clinical study of patients with active ALD that showed reduced liver vitamin B12 levels in spite of elevated serum levels of vitamin B12 and its analogs, suggesting an inability of compromised hepatocytes to retain vitamin B12 stores [52] .…”
Section: Effects Of Alcoholism On Vitamin B6 and B12 Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that alcoholic liver disease patients had low pyridoxine levels with elevated cystathionine and decreased alpha-aminobutyrate/cystathionine ratios, consistent with decreased activity of pyridoxine-dependent cystathionase. 45 Cobalamin is an enzyme cofactor for metabolism of homocysteine to methionine and the metabolism of homocysteine is affected by alcohol abuse. In a recent study, the levels of vitamin B 12 correlated negatively with homocysteine and positively with the markers of alcoholrelated liver injury.…”
Section: Vitamins B 6 B 9 and B 12mentioning
confidence: 99%
“…It was reported that alcoholic liver disease patients had low pyridoxine levels with elevated cystathionine and decreased alpha-aminobutyrate/cystathionine ratios, consistent with decreased activity of pyridoxine-dependent cystathionase. 45 Cobalamin is an enzyme cofactor for metabolism of homocysteine to methionine and the metabolism of homocysteine is affected by alcohol abuse. In a recent study, the levels of vitamin B 12 correlated negatively with homocysteine and positively with the markers of alcohol-related liver injury.…”
Section: Vitamins B 6 B 9 and B 12mentioning
confidence: 99%